abaA, a new pleiotropic regulatory locus for antibiotic production in Streptomyces coelicolor. - Fernández-Moreno, M A (1992)
Production of the blue-pigmented antibiotic actinorhodin is greatly enhanced in Streptomyces lividans and Streptomyces coelicolor by transformation with a 2.7-kb DNA fragment from the S. coelicolor chromosome cloned on a multicopy plasmid. Southern analysis, restriction map comparisons, and map locations of the cloned genes revealed that these genes were different from other known S. coelicolor genes concerned with actinorhodin biosynthesis or its pleiotropic regulation. Computer analysis of the DNA sequence showed five putative open reading frames (ORFs), which were named ORFA, ORFB, and ORFC (transcribed in one direction) and ORFD and ORFE (transcribed in the opposite direction). Subcloning experiments revealed that ORFB together with 137 bp downstream of it is responsible for antibiotic overproduction in S. lividans. Insertion of a phi C31 prophage into ORFB by homologous recombination gave rise to a mutant phenotype in which the production of actinorhodin, undecylprodigiosin, and the calcium-dependent antibiotic (but not methylenomycin) was reduced or abolished. The nonproducing mutants were not affected in the timing or vigor or sporulation. A possible involvement of ORFA in antibiotic production in S. coelicolor is not excluded. abaA constitutes a new locus which, like the afs and abs genes previously described, pleiotropically regulates antibiotic production. DNA sequences that hybridize with the cloned DNA are present in several different Streptomyces species.